The Risk Factors and Their Effects in Ischemic Stroke - Karaman, Esra; Gokhan Turtay, Muhammet; Colak, Cemil; Oguzturk, Hakan; Gurbuz, Sukru; Kamisli, Suat; Celik, Emrah (Annals of Medical Research, 2021)
None